Comparative analysis of effect of methanol and ethanol on Karanja biodiesel production and its optimisation. (15th September 2016) - Verma, Puneet; Sharma, M.P.
Abstract: Extensive use of fossil fuel resources especially petroleum has resulted in situation to look for alternative fuel sources. Biodiesel offers a good choice due to its renewable nature. In recent times, mainly methanol has been used in transesterification reaction for biodiesel production as it is derived from fossil sources, and biodiesel produced cannot be termed as completely renewable while other alcohols such as ethanol, being obtained from renewable sources such as potatoes, sugarcane, grains, corn and sorghum can be used for transesterification reaction. The aim of this work was to investigate the impact of ethanol on biodiesel production from Karanja oil and then optimise process variables for transesterification process. Further a comparison was done in optimised reaction parameters for methanolysis and ethanolysis. The result of experimental investigation shows that Karanja biodiesel yield of 91.05% was achieved with molar ratio of 10.44:1 for methanol using 1.22% w/w KOH as catalyst for 90.78 min at the temperature of 66.8 °C. On the other hand for, ethanolysis, optimised reaction conditions were, 8.42:1 molar ratio, 61.3 °C reaction temperature with 1.21% of catalyst and 120 min of reaction time to obtain yield of 77.4%.